Therapeutic potential of silver nanoparticles from Helianthemum lippii extract for mitigating cadmium-induced hepatotoxicity: liver function parameters, oxidative stress, and histopathology in wistar rats - Laib, Ibtissam; Ali, Boutlilis Djahra; Alsalme, Ali; Croun, David; Bechelany, Mikhael; Barhoum, Ahmed (Frontiers in Bioengineering and Biotechnology, 2024)
This study explored the therapeutic potential of silver nanoparticles (Ag NPs) synthesized with a Helianthemum lippii extract for mitigating cadmium-induced hepatotoxicity in Wistar rats.The results of X-ray diffraction, UV-Vis spectrometry, and energy-dispersive X-ray spectroscopy with scanning electron microscopy confirmed the formation of Ag NPs with a cubic crystal structure and particle size from 4.81 to 12.84 nm. The Ag NP sub-acute toxicity study (2 mg/kg and 10 mg/kg) did not highlight any difference with untreated control rats (n=3 animals/group). Then, adult Wistar rats (n=5/group) were divided into one control (untreated/unexposed) and three experimental groups (Ag NPs alone, exposure to 50 mg/kg CdCl2 in drinking water for 35 days, and exposure to CdCl2 for 35 days followed by 0.1 mg/kg/day Ag NPs by intraperitoneal injection for 15 days). In the CdCl2 exposed group, body weight was decreased, alanine and aspartate transaminase were significantly increased (p < 0.05 vs control), indicating hepatotoxicity, antioxidant defenses were decreased, and malondialdehyde levels increased. Liver architecture was altered (portal fibrosis, inflammation, necrosis, sinusoid and hepatic vein dilation, and cytoplasmic vacuolations). Treatment with Ag NPs after CdCl2 exposure effectively attenuated some of the adverse effects of CdCl2 exposure on liver function and architecture and increased body weight. This study contributes to the research on sustainable and eco-friendly approaches for NP synthesis, addressing toxicity concerns and offering potential applications for therapeutic strategies. It also supports the adoption of green synthesis methods, aligning with the growing emphasis on environmentally conscious practices in scientific research and healthcare.